Pengaruh Pengetahuan Pajak, Self Assessment, Tingkat Penghasilan, dan Tarif Pajak Terhadap Penghindaran Pajak pada UMKM - Lestari, Sri; Trisnaningsih, Sri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines tax knowledge, self-assessment, income level, and tax rates on tax avoidance in the Micro, Small, and Medium Enterprises (MSME) sector. Focusing on the efforts of MSMEs to minimize tax obligations, this quantitative research analyzes the correlation between variables using primary data collected through a questionnaire survey of registered MSME actors, aiming to provide insights into the factors influencing tax avoidance behavior among MSMEs. The study population consists of MSME actors registered in the Digital Data Application for Cooperatives and Micro Enterprises (Ditakopum) in Candi District, Sidoarjo Regency. The sampling type for this research is probability sampling with the method of sample selection being simple random sampling. A total of 81 MSME respondents were obtained from Candi District. The analysis method used is multiple linear regression analysis with SPSS 29 software to test hypotheses. The results of this study show that tax knowledge and tax rates have an impact on tax avoidance. Meanwhile, self-assessment and income level do not have an influence on tax avoidance..